Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

On the monoterpene emission under heat stress and on the increased thermotolerance of leaves of Quercus ilex L. fumigated with selected monoterpenes - Loreto, F.; Förster, A.; Dürr, M.; Csiky, O.; Seufert, G. (Plant, Cell & Environment, 1998)
Leaves of the monoterpene emitter Quercus ilex were exposed to a temperature ramp with 5 °C steps from 30 to 55 °C while maintained under conditions in which endogenous emission of monoterpenes was allowed or suppressed, or under fumigation with selected exogenous monoterpenes. Fumigation with monoterpenes reduced the decline of photosynthesis, photorespiration and monoterpene emission found in non-fumigated leaves exposed to high temperatures. It also substantially increased respiration when photosynthesis and photorespiration were inhibited by low O2 and CO2-free air. These results indicate that, as previously reported for isoprene, monoterpenes may help plants cope with heat stress. Monoterpenes may enhance membrane stability, thus providing a rather non-specific protection of photosynthetic and respiratory processes. Monoterpene emission was maximal at a temperature of 35 °C and was inhibited at higher temperatures. This is likely to be the result of the temperature dependency of the enzymes involved in monoterpene synthesis. In contrast to other monoterpenes, cis- and trans-β-ocimene did not respond to exposure to high temperatures. Cis-β-ocimene also did not respond to low O2 or to fumigation. These results indicate that cis and trans-β-ocimene may have a different pathway of formation that probably does not involve enzymatic synthesis.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: monoterpene emission; monoterpene fumigation; photosynthesis; Quercus ilex; respiration; thermotolerance